Preventing childhood obesity, phase II feasibility study focusing on South Asians: BEACHeS. Issue 4 (10th April 2014) - Adab, Peymané; Pallan, Miranda J; Cade, Janet; Ekelund, Ulf; Barrett, Timothy; Daley, Amanda; Deeks, Jonathan; Duda, Joan; Gill, Paramjit; Parry, Jayne; Bhopal, Raj; Cheng, K K
Abstract : Objective: To assess feasibility and acceptability of a multifaceted, culturally appropriate intervention for preventing obesity in South Asian children, and to obtain data to inform sample size for a definitive trial. Design: Phase II feasibility study of a complex intervention. Setting: 8 primary schools in inner city Birmingham, UK, within populations that are predominantly South Asian. Participants: 1090 children aged 6–8 years took part in the intervention. 571 (85.9% from South Asian background) underwent baseline measures. 85.5% (n=488) were followed up 2 years later. Interventions: The 1-year intervention consisted of school-based and family-based activities, targeting dietary and physical activity behaviours. The intervention was modified and refined throughout the period of delivery. Main outcome measures: Acceptability and feasibility of the intervention and of measurements required to assess outcomes in a definitive trial. The difference in body mass index (BMI) z-score between arms was used to inform sample size calculations for a definitive trial. Results: Some intervention components (increasing school physical activity opportunities, family cooking skills workshops, signposting of local leisure facilities and attending day event at a football club) were feasible and acceptable. Other components were acceptable, but not feasible. Promoting walking groups was neither acceptable nor feasible. At follow-up, children in the intervention compared with the control group were less likely to be obese (OR 0.41; 0.19 to 0.89), and had lower adjusted BMI z-score (−0.15 kg/m 2 ; 95% CI −0.27 to −0.03). Conclusions: The feasibility study informed components for an intervention programme. The favourable direction of outcome for weight status in the intervention group supports the need for a definitive trial. A cluster randomised controlled trial is now underway to assess the clinical and cost-effectiveness of the intervention. Trial registration number: ISRCTN51016370.